EA innovations in managing public sectors: issues & challenges - Hussein, S. S. (International Business Information Management Association, IBIMA, 2016)
Enterprise Architecture (EA) has been identified as one of the prime initiative towards public sector transformation. EA implementation innovates public sector management. However, building upon several public sector agencies that had implemented these initiatives, it was reported as unfavourable in sustaining EA practices. This study aims to i. identify related issues and challenges towards sustainability of EA implementation and ii. to identify factors that influence sustainability of EA practices. Through qualitative approach, six related issues were discerned and six key factors were established in sustaining EA practices in the construction of EA governance framework. With regards to the practical implication, this paper can serve as reference in establishing EA initiatives in the public sector.